On synchronal algorithm for fixed point and variational inequality problems in hilbert spaces - Mohammed, Lawan Bulama; Kilicman, Adem (SpringerOpen, 2016)
The aim of this article is to expand and generalize some approximation methods proposed by Tian and Di (J Fixed Point Appl, 2011. doi:10.​1186/​1687-1812-21) to the class of (k,{μn},{ξn},ϕ)-total asymptotically strict pseudocontraction to solve the fixed point problem as well as variational inequality problem in the frame work of Hilbert space. Further, the results presented in this paper extend, improve and also generalize several known results in the literature.